Innovative Imaging of the Left Atrium in Patients with AF - Rizzo, Toni (MD Conference Express, 2014)
This session addressed innovative imaging methods used for the evaluation and treatment of atrial fibrillation, with a focus on various echocardiography techniques and cardiac magnetic resonance imaging. Improvements in imaging methods have resulted in higher quality atrial imaging, lower radiation exposure, and improved prognosis of outcomes following AF therapy.